Strategi Penyajian Berita Pada Portal pariamankota.go.id - Wafiqah Sabrina; Yusuf Afandi (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2023)
News Presentation Strategy is an effort to convey information to readers in an effective and interesting way, media or news platforms use news presentation strategies.. The main goals of this strategy are to grab the reader's attention, increase participation and engagement, and convey messages clearly and accurately. Presenting news on the pariamankota.go.id portal uses three strategies namely; the first is the strategy of selecting issues, the second is the placement of news issues, the third is the strategy of presenting and developing news. Pariamankota.go.id was created to provide news from the Kota Pariaman government covering the activities of the local government and OPD. This study used a descriptive qualitative research method using the news presentation strategy theory of Kasirul Fadli. Data was collected by means of documentation techniques and observation of news on the pariamankota.Go.Id portal. which leads to reporting on the scope of government activities in Pariaman City. The news that is shared through the pariamankota.go.id portal attracts readers to find out the strategy applied by the portal.